Disposal of dredged sediments in tropical soils: ecotoxicological effects on earthworms - Cesar, Ricardo (2014)
The upper limit concentrations of metals established by international legislations for dredged sediment disposal and soil quality do not take into consideration the properties of tropical soils (generally submitted to more intense weathering processes) on metal availability and ecotoxicity. Aiming to perform an evaluation on the suitability of these threshold values in tropical regions, the ecotoxicity of metal-contaminated dredged sediment from the Guanabara Bay (Rio de Janeiro, Brazil) was investigated. Acute and avoidance tests with Eisenia andrei were performed with mixtures of dredged sediment with a ferralsol (0.00, 6.66, 13.12, 19.98, and 33.30 %) and a chernosol (0.00, 6.58, 13.16, 19.74, and 32.90 %). Mercury, lead, nickel, chromium, copper, and zinc concentrations were measured in test mixtures and in tissues of surviving earthworms from the acute tests. While ferralsol test mixtures provoked significant earthworm avoidance response at concentrations ≥13.31 %, the chernosol mixtures showed significant avoidance behavior only at the 19.74 % concentration. The acute tests showed higher toxicity in ferralsol mixtures (LC50=9.9 %) compared to chernosol mixtures (LC50=16.5 %), and biomass increased at the lowest sediment doses in treatments of both test soils. Most probably, the expansive clay minerals present in chernosol contributed to reduce metal availability in chernosol mixtures, and consequently, the ecotoxicity of these treatments. The bioconcentration factors (BCF) for zinc and copper were lower with increasing concentrations of the dredged sediment, indicating the existence of internal regulating processes. Although the BCF for mercury also decreased with the increasing test concentrations, the known no biological function of this metal in the earthworms metabolism lead to suppose that Hg measured was not present in bioaccumulable forms. BCFs estimated for the other metals were generally higher in the highest dredged sediment doses.